Utilization swamp taro (Cyrtosperma merkusii) in the all-purpose premix sauce production. - Lingco, Geralyn Rusia
The study focused on the utilization of swamp taro (Cyrstoperma merkusii) corm in the all-purpose (AP) premix sauce production. Three formulations with varying amount of boiled taro: (F1 (50 g), F2 (100 g) and F3 (150 g) were subjected to rank test for preference. F2 was significantly preferred (Kramer?s Rank Test at 95% confidence level) over F1 and F3. AP taro premix sauce had a pH of 5.97 and water activity of 0.47. The AP taro premix sauce had a moisture content of 7.29% ash content (14.11%), crude protein (0.62 %), crude fat (2.15%), crude fiber (0.98%) and carbohydrates (74.84%). AP taro premix sauce was reconstituted with water for fishball sauce and chicken gravy preparation in different ratios. For fishball sauce, ATPS-1 (21 g AP taro premix to 235 g water) was significantly preferred over aAPTS-2 (21 g AP taro premix to 235 g water) was significantly preferred over APTS-2(21 g AP taro premix to 350 g water) and had a consistency of 6.80 cm/s. For chicken gravy, APTG-1 (27 g AP taro premix to 235 g water) was consistently preferred over APTG-2 (27g AP taro premix to 350 g water) and had a consistency of 4.05 cm/s. Among 50 respondents, 72% rated the fishball sauce like moderately to like extremely. On the other hand, 98% of the consumers rated the chicken gravy like moderately to like extremely.